Diversity of Uropathogens and their Antibiotic Susceptibility Pattern - Fawad Mahmood, Sajjad Mohammad, Khalida Kousar, Ikram Ullah, Burhan Ahmad, Zahid Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Bacterial urinary tract infection (UTI) is one of the utmost prevailing bacterial diseases that affect both sexes at different ages. Due to emerging multi-drug resistant (MDR) bacteria, it is necessary to investigate the antibiotic susceptibility pattern of the bacterial agents to improve the empirical treatment. In this study, we collected a total of 142 urine samples from infected individuals of both sexes at Al-khidmat diagnostics and blood bank from January to March 2022. Different antibiotic susceptibility patterns of the bacterial isolates were examined by using the disk diffusion method. The UTI was reported in 21 (15 %) males and 119 (85 %) females. the highest number of positive individuals are found in middle and old age groups respectively 40 % and 44 %. While 96 % of uropathogens are gram-positive and only 3 % of cases were caused by gram-negative bacteria. The most prevalent pathogen was E.coli 62 % and followed by Staphylococcus Aureus 12 %.In study showed that E.coli is 62 % amoxicillin, Cefuroxime 23, Cefixime 48 %, Norfloxacin 24, Penicillins 37 % , Ciprofloxacin 24 %, Gentamycin 8 %, Ceftriaxone 20 %, and Levofloxacin 4 % resistant. The current study concluded that antibiotic resistance among urinary pathogens was raised, and significant variance in antibiotic susceptibility patterns was identified. UTIs can be treated with medicines such as Levofloxacin, Gentamycin, Teicoplanin, and Moxifloxacin. This study’s findings indicate that future research should focus on the causes of resistance to identify solutions to this crucial problem, as well as on the use of health education to prevent drug usage. Keywords: Uropathogens, Antibiotics, Urinary tract infection, UTI, MDR